Influence of Welding Parameters on Macrostructure, Microstructure and Mechanical Properties in Orbital Pipe Welding of A36 Mild Steel Pipe - Baskoro, Ario Sunar; Kiswanto, Gandjar; Widyianto, Agus; Panji, Muchamad (International Journal of Integrated Engineering, 2021)
In this work, the influence of welding parameters on macrostructure, microstructure and mechanical properties in Gas Tungsten Arc Welding (GTAW) orbital pipe welding was investigated. The aim of this study was to evaluate the effect of GTAW orbital pipe welding parameters on macrostructure, microstructure and tensile strength. This experiment using A36 mild steel pipe material with a thickness of 0.6 mm and an outer diameter of 114.3 mm. The joining method used is the V-groove join without gaps with the ER70-S 6 wire feeder. Welding results were analyzed in macro and micro graphs, as well as analysis of tensile strength. Macro-graphic analyses revealed the depth of weld penetration that occurs as well as the boundaries of each welding area. The micro-graphic analysis shows structural changes that occur in the welding area. Welding parameters with a welding current of 170 A, a welding speed of 0.9 mm/s and a welding position of 0Â° have a Ultimate Tensile Strength (UTS) increase of 11.01% over the base metal. The highest and lowest UTS are 502.80 MPa and 280.77 MPa, respectively. The fracture surface in the weld area shows that many micro-voids and dimples were formed.